Sexual Intercourse during Pregnancy among Postpartum Women Admitted to the Department of Obstetrics in a Tertiary Care Centre - Bibechan Thapa; Smrity Maskey Pradhan; Meenu Maharjan; Aakriti Pandey; Kamana Sen; Shreyasi Karki; Prajwal Pudasaini; Anu Tiwari (Journal of Nepal Medical Association, 2023)
Introduction: Pregnancy is a time when women's bodies and minds go through a lot of changes. Sexuality is an important part of a woman's health and well-being, and it often changes during pregnancy. Most women admit that their libido changes in some way during pregnancy. However, the sexuality of a pregnant woman is very individual and influenced by a variety of different factors. This is a very important topic that is often taboo, especially in a male-dominated society, and it needs to be explored more. The aim of this study was to find out the prevalence of sexual intercourse among postpartum women admitted to the Department of Obstetrics in a tertiary care centre.